Factors Associated With Hospital Admissions and Readmissions in Patients With Gastroparesis Using the Nationwide Readmission Database. Issue 9 (October 2020) - Shahsavari, Dariush; Zhao, Huaqing; Ehrlich, Adam C.; Zoll, Bryan E.; Lu, Xiaoning; Malik, Zubair; Parkman, Henry P.
Abstract : Background: Gastroparesis can be associated with severe symptoms. Health care utilization for gastroparesis has increased in part due to an increase in hospital admissions. Goals: To characterize patients admitted for gastroparesis-related symptoms and determine risk factors associated with 30-day readmissions. Study: The Nationwide Readmission Database (NRD) for the year 2014 was used to identify patients admitted to hospitals using the International Classification of Diseases (ICD)-9 code for gastroparesis as primary diagnosis or as the secondary diagnosis with first diagnosis code of a gastroparesisrelated symptom. Logistic regression was used to determine risk factors associated with 30-day readmission. Results: There were 5268 gastroparesis patients admitted with the average length of stay (LOS) of 5.4±6.6 days. Age averaged 48.9±18.1 years, 73.8% were female individuals, and 31% had diabetes. Inpatient mortality was 0.4%. The overall 30-day readmission rate was 6.2%. Longer LOS [odds ratio (OR)=1.4; 95% confidence interval (CI), 1.0-1.9], younger age, drug abuse (OR=1.6; 95% CI, 1.2-2.2), and marijuana use (OR=1.7; 95% CI, 1.0-2.7) were associated with increased risk of 30-day readmission. Female gender ( P =0.083), opioid use ( P =0.057), and admission to larger hospital ( P =0.070) showed a trend toward higher readmission rates. Older patients, and patients with hypertension and diabetes showed lower rates of readmission. Conclusions: Use of the Nationwide Readmission Database (NRD) allows better understanding of gastroparesis admissions and readmissions. Average hospital stay was 5.4 days with 0.4% mortality rate. Overall 30-day readmission rate was 6.2%. Higher LOS, drug abuse, and marijuana use increased the 30-day readmission rate. Diabetes, hypertension, and older age were associated with lower readmissions.